Food prices and marketing margins during the COVID‐19 pandemic: Evidence from vegetable value chains in Ethiopia - Hirvonen, Kalle; Minten, Bart; Mohammed, Belay; Tamru, Seneshaw (International Association of Agricultural Economists, 2021)
It is widely feared that the shock of the COVID‐19 pandemic will lead to a significant worsening of the food security situation in low and middle‐income countries. One reason for this is the disruption of food marketing systems and subsequent changes in farm and consumer prices. Based on primary data in Ethiopia collected just before the start and a few months into the pandemic, we assess changes in farm and consumer prices of four major vegetables and the contribution of different segments of the rural‐urban value chain in urban retail price formation. We find large, but heterogeneous, price changes for different vegetables with relatively larger changes seen at the farm level, compared to the consumer level, leading to winners and losers among local vegetable farmers due to pandemic‐related trade disruptions. We further that despite substantial hurdles in domestic trade reported by most value chain agents, increases in marketing—and especially transportation—costs have not been the major contributor to overall changes in retail prices. Marketing margins even declined for half of the vegetables studied. The relatively small changes in marketing margins overall indicate the resilience of these domestic value chains during the pandemic in Ethiopia.